Exploring the Ethical Constructs of Dental Patients to Guide Dental Ethics Teaching - Muhammad Imtiaz, Usman Mahboob, Rehan Ahmed Khan, Rahila Yasmin, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To explore the ethical constructs of dental patients to guide dental ethical teaching. Methodology: A grounded theory approach, inspired by the socio-constructivist paradigm was used for data collection. The duration of the study was six months and non-probability, purposive, convenience was used. Dental patients, visiting the various departments of dental colleges in Lahore, Pakistan, were interviewed to explore their ethical constructs and thematic analysis was done. Results: Nineteen dental patients were interviewed. Three themes were derived from four hundred and sixty-two codes. Three themes were: dental patient ethical constructs, dental ethics teaching, and ethical context. Honesty, good communication ethics and respect for patients were the main ethical constructs of dental patients. Dental patients also emphasized effective ethics teaching and assessment. Finally, for dental patients, religion and economic condition were two main contextual factors affecting ethical constructs. Conclusion: Dental patients desire honesty, good communication ethics, and respect for patient from dental students. The patients defined ethical context and ethical constructs may help curriculum developers to contextualize and emphasize dental ethics teaching. Religion and the financial aspect are the two contextual factors effecting ethical construct that play key roles. Keywords: Dental ethics, dental patients, dental ethics teaching, dental curriculum, ethical context, dental patients’ ethical constructs.